The Influence of Organizational Commitment and Work Environment on Employee Turnover in the Export Department at PT Adis Dimension Footwear, Tangerang Regency - Kholish, Irfan Nur; Soebadio, Bizzma Buana Amriki; Setiawan, Temmy (IJOSPOL - International Journal of Social, Policy and Law, 2026)
This study aims to determine the extent of influence of organizational commitment and the work environment on employee turnover in the Export department of PT. Adis Dimension Footwear, Balaraja, Tangerang.The author employed an associative method with a quantitative descriptive approach, where a sample was drawn from a population and a questionnaire served as the primary data collection tool. The data collection technique used a questionnaire for 45 (forty-five) respondents using a Likert scale and SPSS version 26.The results of this study indicate that (1) partially, organizational commitment significantly influences employee turnover in the Export department of PT. Adis Dimension Footwear, Balaraja, Tangerang, as indicated by the calculated t-value > t- table (2.848 > 2.018) and a significance value of 0.000, which is less than 0.05. Thus, Ha is accepted and H0 is rejected. (2) partially, the work environment significantly influences employee turnover in the Export department of PT. Adis Dimension Footwear Balaraja-Tangerang, as indicated by the calculated t-value > t-table (4.827> 2.018) and a significance value of 0.000, which is less than 0.05. Therefore, Ha is accepted and H0 is rejected. (3) Simultaneously, organizational commitment and work environment significantly influence employee turnover in the Export department at PT. Adis Dimension Footwear Balaraja-Tangerang, as indicated by the calculated F- value > F-table (66.089 > 3.17) with a significance level of 0.000. Therefore, Ha is accepted and H0 is rejected.Based on the research results, it can be concluded that the variables of organizational commitment and work environment, both partially and simultaneously, have a significant influence on employee turnover in the Export department at PT. Adis Dimension Footwear Balaraja-Tangerang.